Perbandingan Adverbia Issou, Nao, dan Sara ni dalam Bahasa Jepang - Made Henra Dwikarmawan Sudipa (Diponegoro University, 2020)
This research aims to analyze the meaning of issou, nao, and sara ni. These three words are Japanese adverbs which having the same lexical meaning ‘furthermore’, but contextually the meanings are different. The data were collected from article posted on website asahi.com by observation method and note-taking techniques. They were analyzed using distribution method with expansion techniques. The meanings of these three adverbs were analyzed using contextual meaning theory by Pateda (2001) The results show that issou, nao, and sara ni have the same meaning that is 'something more than before’. The difference is on the spesific context. Nao can be used to indicates a state that still continuing until now without any much improvement. Sara ni. Can be used to indicates addition of something that already sufficient.